Aplicação do método dos elementos finitos para análise da influência do bloco de coroamento na distribuição de deformações, tensões e recalques de um grupo de estacas escavadas - Silva, Boniex Manoel da (Universidade Federal Rural do Semi-Árido, 2019)
Groups of floating piles are foundations elements made to possess large load capacity and, in most theoretical analyzes, the contribution of their pile cap is neglected. Given the physical complexity involved in geotechnical problems in civil engineering, it is common to simplify the mathematical models to carry out the structural analyzes. Thus, numerical methods emerged as an interesting alternative to the study of foundations. Today, it is possible to simulate computationally the behavior of soils when subjected to the most varied types of loads. In this work, 6 arrangements were made for the type of foundation mentioned, where, using the Finite Elements Method, through Ansys multiphysics analysis software, the behavior of the structure and soil was studied when submitted to a vertical load, considering the soil-structure interaction. For the modeling of the geometric models of the foundation, variations of the position of the pile cap were made, which could be supported, buried or suspended on the ground, with the intention of understanding how the element of union of the piles influences the behavior of the soil and the structure, through the analysis of the distribution of tensions and deformations of the set. Also, a soil analysis was carried out in a purely elastic regime, to compare the structural settlement with that predicted by the theoretical models. The results showed that the stiffness of the cap has great influence on the deformation and distribution of bending moments in the piles, being able to alter its algebraic sign. It was verified that the use of cap in contact with the soil, while reducing the compression load on the piles, negatively affects the friction efficiency between soil and concrete, and can reduce the load capacity of the structure. It was also found that perfectly elastic soils have a divergent behavior to the real cases, which shows that the methods based on elasticity theory applied to granular materials should be used carefully.
Monografia
Keywords: Ansys; Estacas; Fundações; Numérica; Simulação; Ansys; Foudations; Numerical; Piles; Simulation; ENGENHARIAS::ENGENHARIA CIVIL